Choice Both Affects and Reflects Preferences. Issue 7 (July 2014) - Coppin, Géraldine; Delplanque, Sylvain; Bernard, Charlène; Cekic, Sezen; Porcherot, Christelle; Cayeux, Isabelle; Sander, David
The free-choice paradigm is a widely used paradigm in psychology. It has been used to show that after a choice between two similarly pleasant stimuli, the pleasantness of the chosen one tends to increase, whereas the pleasantness of the rejected one tends to decrease—a spreading of alternatives. However, the methodological validity of the free-choice paradigm to study choice-induced preference change has recently been seriously questioned [Chen, K. M., & Risen, J. L. (2010). How choice affects and reflects preferences: Revisiting the free-choice paradigm. Journal of Personality and Social Psychology, 99, 573–594. doi:10.1037/a0020217]. According to this criticism, the classically reported spreading of alternatives between the first and second rating sessions cannot be unambiguously interpreted to reflect a true change in preferences and can be observed even for completely static preferences. Here, we used two measurement sequences, a classical Rating 1–choice–Rating 2 sequence and a control Rating 1–Rating 2–choice sequence, to disentangle the spreading of alternatives driven by the effect of choice from the artefactual effect highlighted by Chen and Risen. In two studies using different stimulus material (faces and odours), we find that choice has a robust modulatory impact on preferences for rejected odours, but not for chosen odours and not for faces.